Sacrococcygeal teratoma with unilateral renal agenesis, spinal dysraphism, lumbar hernia, CTEV and natal teeth - Rahul Gupta; Arun Kumar Gupta (Formosan Journal of Surgery, 2019)
We report a unique case of unilateral renal agenesis, spinal dysraphism, lumbar hernia, congenital talipes equino varus, and natal teeth associated with sacrococcygeal teratoma (SCT). The occurrence of this rare association in a neonate has not been reported in the literature. The theory of defective mesenchymal precursor cells from primitive node may explain the presence of associated malformations (related to defective mesenchyme) and presence of SCT.